2008
DOI: 10.1021/nn800283u
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Resistance and Field Emission Performance of Individual ZnO One-Dimensional Nanostructures

Abstract: Both electrical and field emission measurements were carried out to study the correlation between resistance and field emission performance of individual one-dimensional (1D) ZnO nanostructures. Three types of 1D ZnO nanostructures were investigated (i.e., agave-like shape, pencil-like shape, and hierarchical structure) and were prepared by thermal chemical vapor transport and condensation without using any catalyst. The 1D ZnO nanostructures have obvious differences in resistance and thus conductivity from ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 29 publications
1
94
1
1
Order By: Relevance
“…An emission current density of 1 mA cm À2 (the minimum required to produce a luminescence of 300 cd m À2 for a video graphics array field-emission display with a typical high-voltage phosphor screen efficiency of 9 lm W À1 ) is achieved at 3.8 V mm À1 , which is also very low compared to other reported values. [8][9][10][11][12][13][14][15][16][17][18] Additionally, the emitting current density can be as high as 2.5 mA cm À2 , which is the highest among all the reported to date. [8][9][10][11][12][13][14][15][16][17][18] The corresponding Fowler-Nordheim (F-N) plot fits well to a line.…”
Section: Improvement Of Field Emissionmentioning
confidence: 90%
See 2 more Smart Citations
“…An emission current density of 1 mA cm À2 (the minimum required to produce a luminescence of 300 cd m À2 for a video graphics array field-emission display with a typical high-voltage phosphor screen efficiency of 9 lm W À1 ) is achieved at 3.8 V mm À1 , which is also very low compared to other reported values. [8][9][10][11][12][13][14][15][16][17][18] Additionally, the emitting current density can be as high as 2.5 mA cm À2 , which is the highest among all the reported to date. [8][9][10][11][12][13][14][15][16][17][18] The corresponding Fowler-Nordheim (F-N) plot fits well to a line.…”
Section: Improvement Of Field Emissionmentioning
confidence: 90%
“…In reality, the FE properties are affected by many parameters, for example, the radius of curvature of a single emitter, the uniformity and density of the emitters, [8][9][10][11][12][13][14][15][16][17][18] and so forth. These factors could be simultaneously controlled by the presently developed method for ultimate improvements in field emission.…”
Section: Improvement Of Field Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…indicated that the conductivity of the cold cathode is a very important factor affecting fi eld emission properties. [ 26 ] The conductance of the TONWs was roughly studied through a carbon cloth-TONW-Cu plate sandwich structure which is shown in the upper inset of Figure 3b . From the I -V curve shown in Figure 3b , we can calculate the resistance of the carbon cloth-TONW-Cu plate sandwich structure which is only 3.22 Ω .…”
mentioning
confidence: 99%
“…[12] Eine interessante neue Entwicklung geht auf Xu und Mitarbeiter zurück, die zeigten, dass feine Unterschiede bei einzelnen eindimensionalen ZnO-Nanostrukturen zu ausgesprochen unterschiedlichen elektrischen und Feldemissionseigenschaften führen. [13] Viele Synthesemethoden -von konventionellen Festkör-persynthesen bis zu modernen Verfahren wie der physikalischen Gasphasenabscheidung -wurden zur Herstellung definierter ZnO-Nanostrukturen genutzt. [2c,d] Mit ihrem katalysatorfreien Dampf/Festkörper-Wachstumsverfahren wurden Wang et al zu Wegbereitern der Synthese von eindimensionalen ZnO-Nanomaterialien wie Nanogürteln und Nanofedern mit Längen von mehreren zehn bis einigen hundert Mikrometern.…”
unclassified